Towards the five hundred years of the first baptism in the Philippines : integrating the nine pastoral priorities of the church in the spirit of new evangelization - Tawatao, Anthony Paul R. (Mary Help of Christians Theology Seminary : [s.n.], 2020)
The focus of this study is to integrate the nine pastoral priorities of the Church in the Philippines through the four principles of the New Evangelization: encountering Christ, conversion, sense of belongingness or communion, and zeal for mission to show that every pastoral priorities of the Church should always anchor on the New Evangelization The Church leaders of the Catholic faith in the Philippines gathered together a decade after PCP II was promulgated, they enumerated the nine pastoral priorities that the Church in the Philippines must focus on yearly until the five hundredth year anniversary of Christianity in the country. The nine pastoral priorities are: Integral Faith Formation (2013); the Laity (2014), the Poor (2015); the Eucharist and the Family (2016); the Parish as a Communion of Communities (2017); the Clergy and Consecrated Persons (2018), the Youth (2019); Ecumenism. Interreligious Dialogue and Indigenous People (2020); and Missio ad Gentes (2021). The Philippine Church is still in the battle of so many flaws that are unchanged in some respects. The great factors are weakness in formation and education, lack of defined pastoral directions and programs, deficiencies in structures and the non-implementation of the many prescriptions in PCP II. Even though there are many aspects that were found lacking in the mission of evangelization, the focus should not be on the negative outcomes, but rather on the great abundance of God's gift of renewal.
Bibliography: pages 148-154.
CHED-La Union
Keywords: Pastoral theology